The price of punishment: Days missed due to suspension in U.S. K‐12 public schools. Issue 10 (1st June 2021) - Fabes, Richard A.; Catherine, Evandra; Quick, Matthew; Blevins, Darielle; Musgrave, Aryn
Abstract: The number of days missed due to suspensions (DMS) was analyzed in a national sample of K‐12 public schools in the U.S. In the 2017–2018 national sample, about 11 million days of school were missed due to suspension. Rates of DMS varied across the regions of the U.S., from state to state, and from school to school (greater in nonelementary and non‐charter public schools). Additionally, disparities were found with higher rates found for boys relative to girls and for Black children relative to White children. Regression analyses revealed that school characteristics explained the greatest amount of variance in rates of DMS, although enrollment characteristics also accounted for a significant amount of the variance. It was concluded that there is a need to for more research to better understand the factors that predict DMS and its adverse outcomes for students and to help develop effective prevention and intervention efforts to reduce its use, especially to reduce disparities in its use.